The Financial Analysis of Albazia falcataria Nurseries (The Case Study at UD Sarana Rejeqi, District of Banyumas) - Widowati, Indah; Surata, Agus (Agros Journal of Agriculture Science, 2017)
The purpose of this research was to determine the revenue, cost, profit, accounting rate of return, payback period, and net present value on the agribusiness of Albazia falcataria nursery in UD. Sarana Rejeqi at district of Banyumas, in 2016. The data was collected by interviewing the management staffs, and being analyzed by accounting and cash flow method, and tabel. The result indicated that the revenue of Albazia falcataria seedling business in UD Sarana Rejeqi was IDR 60.000.000 per year with the cost of IDR 44.856.666,67 per year, the profit was IDR 15.143.333,33, one year payback period, and NPV was IDR 1.222.000 and the project was feasible.Â Key-words:Â  Albazia falcataria, NPV, payback period